Acute Encephalitis Syndrome and its alleged litchi (Litchi chinensis) connection—A review and status - VISHAL NATH; SWATI SHARMA; KALYAN BARMAN (The Indian Journal of Agricultural Sciences, 2016)
In recent times, Acute Encephalitis Syndrome (AES), an unexplained mysterious disease is affecting people, especially young children below the age of 15 years in few Asian countries. Several hypothesis and causal factors are being suspected and studied by the researchers.Despite the stringent efforts, the causal agent of AES has not been identified till date and researchers all over the world are striving to find out the cause and remedy of this fatal disease. The concurrence of the AES, in temporal dimensions in most of the places and spatial dimension in few cases with the seasonal maturity of litchi (Litchi chinensis Sonn.) fruits has occasioned in the fruit being associated and judged as a possible causal agent of AES. However, the delicious litchi fruit has been consumed since centuries and thus the alleged association wants critical examination and investigation. The symptoms of the AES disease point towards a viral etiology, and several of the enteroviruses are known to cause encephalitis. This review article is an attempt to present the various supposed causal factors of AES, the critical gaps that question the association between the litchi fruits and AES and some of the serious misgivings to refute the suspected association between the consumption of litchi fruits and AES.